Mechano-activation and Acid Leaching of Li from Alpha Spodumene - Lim, Norman (Curtin University, 2023)
This thesis investigates the mechano-activation of alpha spodumene using PM 100 planetary mill. Li solubilisation was compared with using sulphuric acid versus citric acid on leaching of mechano-activated spodumene. The co-leaching of Al,Fe and Si were also looked into.